PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIVE INTEGRATED READING AND COMPOSITION (CIRC) TERHADAP KETERAMPILAN MENULIS KARANGAN NARASI SISWA KELAS IV SD - Sri Purniati; Eti Sunarsih; Rien Anitra (STKIP Subang, 2024)
This research aims to: 1) To determine the differences in narrative essay writing skills between classes that use the CIRC model and classes that use direct learning in teaching narrative essay writing skills for fourth grade elementary school students; 2) To find out how much influence using the CIRC model has on the narrative essay writing skills of fourth grade elementary school students. The research method used is experimental research with a Nonequivalent Posttest-Only Control Group Design. The population in this study were fourth grade students at SD Negeri 03 Selakau Tua. Total sampling technique sampling. The sample used was all fourth grade students at SD Negeri 03 Selakau Tua. The instrument in this research was a test question sheet. Data analysis for the first hypothesis uses a 2 sample t-test and for the second hypothesis uses an effect size. The results of the research show that: 1) the CIRC learning model for students' narrative essay writing skills provides differences in narrative essay writing skills between classes that use direct learning in class IV of SD Negeri 03 Selakau Tua. This is shown by the t test which shows that t count > t table= 11.501>1.679 means Ha is accepted and Ho is rejected; 2) the CIRC type cooperative learning model has a big influence on students' narrative essay writing skills as indicated by Es, namely 2.358 with high criteria. Based on the research results, it can be concluded that the CIRC learning model has an effect on students' narrative essay writing skills because there is an expected increase in students' narrative essay writing skills.